Security Index II - Mojanoski T., Cane; GJurovski, Marjan (UNIVERSITY “ST. KLIMENT OHRIDSKI” BITOLA FACULTY OF SECURITY SKOPJE KONRAD ADENAUER FOUNDATION SKOPJE, 2018)
This is our second edition of the Security Index, an attempt at demonstrating the complexity and the numerous concepts of security. Our aim is to show how difficult it is to find common characteristics, i.e. to define a set of indicators for warning, reporting or announcing change with a sufficient degree of certainty. The Security Index was designed as an instrument to help decision-makers assess the level of security in the Republic of Macedonia1. It represents an attempt at devising a synthetic indicator, based on a set of indicators, that notifies them of the necessity to find answers. What those answers will be depends on the overall circumstances at hand, the material and technical equipment and human resources available, as well as on the dedication to the duty to identify the essence of a situation and to take action accordingly, utilising the right resources and potentials to create the conditions for the system to function without hindrance. Hence, in our approach, we insist on identifying a certain number of indicators by means of which we can rate the security level in the Republic of Macedonia, so that users of the Index, as well as responsible authorities, can assess the level of compliance with the standards. Thus, within the limits of their responsibility, they would have a clear picture of the situation as well as further measures for maintaining, improving or enhancing security. First and foremost, the Index has to be considered as an instrument that will be useful for its users, helping them to observe the security building process regarding the responsibilities of the state and other competent institutions. 1 “With the Prespa Agreement signed on 17th of June 2018, the process for changing the constitutional name of the Republic of Macedonia officially started. The agreement took effect on 12.02.2019. Due to the fact that the Security Index II was prepared before the agreement took effect throughout the text the name “Republic of Macedonia” will be used.” 12 The Security Index should help us understand and improve the concept of security assessment and to design a system of indicators that point at concrete phenomena significant for observing the compliance with existing standards or detecting the necessity of establishing new ones. At the same time, the Index is designed for a better understanding of the complex social, legal, economic and security indicators. It addresses key information that requires data collection and observation in the process of assessing the Republic of Macedonia‘s security. The necessity of designing this instrument resulted from previous studies of the Faculty of Security (Skopje) and the continuous monitoring of the complex security processes in the Republic of Macedonia during more than forty years. The Index is composed of a number of indicators, and, with its multidimensional assessment concept, devised as a synthetic indicator to notify of current situations and to encourage finding answers and offering solutions for managing them and maintaining a functioning, effective system. Hence, it is a combination of certain indicators with the aim of giving an overview of the complex reality. The study results presented in this edition extend and reinforce the indicator framework which the Security Index is based on. The gained results point to certain situations, notify us of some manifest forms and indicate the need of adequate measures. Again, we would like to use the occasion to thank Johannes Rey, Head of the Konrad Adenauer Foundation‘s office in Skopje, and his colleagues for their continuous support, which represents a direct contribution to the development of approaches to security SECURITY INDEX II 13 and stabilisation in the Republic of Macedonia. We would like to extend our gratitude to the Research and Education Board, the Dean of the Faculty of Security (Skopje), Prof. Dr. Nikola Dujovski, and the reviewers, Prof. Dr. Trajan Gocevski of the Faculty of Philosophy at the Ss. Cyril and Methodius University in Skopje, and Prof. Dr. Zhidas Daskalovski of the Faculty of Security (Skopje) of the “St. Kliment Ohridski” University in Bitola.